A Case Report of Coronary Arteriovenous Fistulas with an Unruptured Coronary Artery Aneurysm Successfully Treated by Surgery. (28th November 2012) - Takeuchi, Nobuhiro; Takada, Masanori; Nishibori, Yoshiharu; Maruyama, Takao
Abstract : A 58-year-old female with a history of Wolff-Parkinson-White syndrome presented at our institution with palpitations and chest pain. Electrocardiography revealed paroxysmal supraventricular tachycardia with a heart rate of 188 beats/min. Antiarrhythmic drugs were ineffective, and tachycardia was resolved by electrical cardioversion. Transthoracic echocardiography revealed abnormal vessels around the right coronary artery (RCA) and pulmonary artery (PA); in addition, we suspected coronary arteriovenous fistula (CAVF). Coronary angiography and coronary computed tomography revealed dilated fistula vessels, with a 1 cm saccular aneurysm around the RCA, originating from the proximal RCA and left anterior descending artery into the main trunk of PA. Therefore, we confirmed the diagnosis of CAVF with an unruptured aneurysm. We surgically ligated and clipped the fistula vessels and resected the aneurysm. The resected aneurysm measured 1 × 1  cm in size. Pathological examination of the resected aneurysm revealed hypertrophic walls comprising proliferating fibroblasts cells thin elastic fibers. Very few atherosclerotic changes manifested in the aneurysm walls. We report the case of a patient with CAVF and an unruptured coronary artery aneurysm who was successfully treated by surgery.